2021
DOI: 10.1136/neurintsurg-2021-017937
|View full text |Cite
|
Sign up to set email alerts
|

Interventional and surgical management of internal jugular venous stenosis: a narrative review

Abstract: BackgroundA small subset of patients with presumed idiopathic intracranial hypertension are found to have isolated internal jugular vein stenosis (IJVS).ObjectiveTo review the current interventions used in patients who present with intracranial hypertension secondary to IJVS.MethodsIn December 2020, we performed a literature search on Pubmed/Medline and Scopus databases for original articles studying surgical and endovascular interventions used for intracranial hypertension in the setting of internal jugular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…A previous study indicated that dehydration and medication could not be devoted to sustained improvement in the patient's symptoms from IJVS 5 . While endovascular stenting was considered as a useful therapy on correcting abnormal elevated ICP induced by venous sinus stenosis, evidence regarding stenting to correct IJV stenosis is still lacking 4,31,32 . Our study reported in 2018 confirmed that endovascular stenting could effectively correct IJV stenosis and remove IJV stenosis‐related symptoms and signs 11 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…A previous study indicated that dehydration and medication could not be devoted to sustained improvement in the patient's symptoms from IJVS 5 . While endovascular stenting was considered as a useful therapy on correcting abnormal elevated ICP induced by venous sinus stenosis, evidence regarding stenting to correct IJV stenosis is still lacking 4,31,32 . Our study reported in 2018 confirmed that endovascular stenting could effectively correct IJV stenosis and remove IJV stenosis‐related symptoms and signs 11 .…”
Section: Discussionsupporting
confidence: 54%
“… 5 While endovascular stenting was considered as a useful therapy on correcting abnormal elevated ICP induced by venous sinus stenosis, evidence regarding stenting to correct IJV stenosis is still lacking. 4 , 31 , 32 Our study reported in 2018 confirmed that endovascular stenting could effectively correct IJV stenosis and remove IJV stenosis‐related symptoms and signs. 11 In this study we further confirmed the effect of endovascular stenting on correcting IJV stenosis by a small self‐controlled sample in the cohort of patients with IJV stenosis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Intracranial venous hypertension can also be secondary to extracranial venous stenosis, specifically the internal jugular vein (IJV) (59). This can be in the setting of a congenitally diminutive IJV, or secondary to extrinsic compression, such as by the styloid process, a cervical rib, hypertrophic scale muscles, or the mastoid process (60,61). At present, there is limited evidence on the surgical treatment of intracranial venous congestion secondary to internal jugular vein stenosis, with no randomized trial data as of yet.…”
Section: Jugular Vein Stenosismentioning
confidence: 99%
“…The paucity of systematic studies invites future thoughtful investigation. 54 The condylar system is a major source of physiologic outflow, especially in non-supine positions figure 1 and figure 12A-F). 51 55 Its prominence varies, and is usually greater with C1 level jugular narrowing (figure 12D-F).…”
Section: Clinical Neurologymentioning
confidence: 99%